Terminal Guidance with Attack Time and Impact Angle Constraints for Hypersonic Vehicle in Dive Phase - Zhao-ting Li; Hong-bo Zhang (International Journal of Aerospace Engineering)
The terminal guidance problem of hypersonic gliding missiles under multiple constraints was considered regarding a coordinated attack in time and space. In this paper, a three-dimensional terminal guidance method based on the real-time updating of parameters is proposed with consideration to the attack time and terminal angle. By this method, the three-dimensional motion was decomposed into the horizontal and vertical plane. In each plane, a real-time solution of the optimal trajectory yielded angle commands that satisfied the terminal angle constraints. Additionally, the time was controlled by changing the flight path angle in the front section of the vertical plane. The results obtained by numerical simulation indicated the good applicability and robustness of this method.